Profesionalisme Guru Pada Era Otonomi Daerah - Sholatul Hayati (Prodi Pendidikan Agama Islam STIT Al-Khairiyah Cilegon, 2018)
Education is a long-term human investment. Educational issues related to hardware, namely the facilities and infrastructure of the learning process, and the software (educational staff or teachers) need to get the attention of the government. However, it seems that many policymakers in this country have not realized the importance of increasing the allocation of the education budget adequately. The quality of human resources can be improved if there are various educational institutions, from elementary school education, SLP, SLA to high-quality universities. One way to improve the quality of educational institutions is by increasing the competence of teachers adequately so that teachers become professional educators. Thus, there is a causal or causal relationship between improving the quality of teachers (professionals) with the successful implementation of regional autonomy. In reality, the world of education in Indonesia is not only required to create human resources that can meet the needs of the implementation of the regional autonomy program. But no less important is the birth of human resources who will be able to compete or talk in the era of economic globalization when the implementation of free trade (WTO) and free trade at the ASEAN level.